The Importance of Remote Sensing Technology and its use in the Study of Environmental Systems (Detection of Groundwater, Model). (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The main objective of this research know is to evaluate the ability remote sensingtechniques to detect ground water in the study area.To achieve this goal, Americansatellite imagery (Landsat-7) was used to cover the study area.And use of the digital image processor program (ERDAS IMAGINE)(EarthResources Data Analysis System)in order to improve aerial image and the signatureof the real coordinates of the area and classified according to the nature of the region,then analyze this image by comparing them with geophysical methods used to identifygroundwater wells.This analysis of the ability of remote sensing techniques and digital image processinghas proven to identify groundwater sites depending on the study and classification ofthe surface crust covering the area, which provides an effective tool for exploringgroundwater.